PENGARUH MOTIVASI, PERSEPSI, SIKAP KONSUMEN DAN PEMBELAJARAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE âBLACKBERRYâ (Studi Pada Masyarakat di Kota Semarang) - Asa Bangkit Probo Pratista, 0625020025; Maskur, Ali (Students Journal of Economic and Management, 2014)
The development of technology, especially mobile technology today, that is worthy of attention, this is because almost all mobile phone to know the age limit , and even almost all walks of life use cell phones in their everyday lives , in connection with it, the BlackBerry nowadays become trend in society Indonesia, Semarang in particular.This study examined how the influence of consumer motivation, consumer perception, consumer attitudes and consumer study on purchasing decisions smartphones " BlackBerry " (Studies in Society in the city of Semarang). The study population of Semarang society. In this study sampling was done by using accidental sampling method. This technique is a sampling technique that is derived from those who are in the scope. Thus mean of samples taken is Semarang society who happen to be found and purchased a BlackBerry smartphone in a few Mall in Semarang. Based on research by the author suggests that there is a positive and significant influence between consumer motivation to purchase decision, there is a positive and significant influence between consumer perception on purchase decisions, there is a positive but not significant effect between consumer attitudes toward purchasing decision, there are positive but not significant effect learning between consumers on purchasing decisions, there is a positive and significant effect between the variables of motivation, perception, consumer attitudes and learning together influence the purchase decision variable, coefficient of determination is the Adjusted R Square in the amount of 16.7 % . This means that made ââquestions of all variables in this study is only able to express by 16.7 % of the total purchase decision while the remaining 83.3 % is influenced by other variables not included in this study as brand association, brand loyalty and brand equity. Keywords: consumer motivation, consumer perception, consumer attitudes, consumer learning and purchasing decisions